FORTIFIKASI EKSTRAK KULIT JERUK BALI PADA SUSU TINGGI KALSIUM: TEROBOSAN BARU DALAM PENGATASAN OSTEOPOROSIS PADA WANITA MENOPAUSE, TERUJI IN VIVO DAN MOLECULAR DOCKING - Dianingati, Ragil Setia; Novarina, Annisa; Hana, Amanita Khoiril; Muntafi’ah, Laeli (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Osteoporosis has one of the cause is lack of estrogen hormone. Commonly prevention therapy is by consuming high calcium milk, but it is not effective. Bali orangeâs peel (Citrus maxima Merr.) is a waste material but contains phytoestrogen according to previous study. Considering of this result, fortification of high calcium milk and bali orangeâs peel is expected to be an effective solution for osteoporosis in menopause woman. This research began with extraction of bali orangeâs peel (BPE) in ethanol 70% by using maceration method. Ovariectomized Sprague dawley female rats are the model of post menopausal woman were treated by BPE for 28 days. The doses of BPE was given to rats 500 and 1000 mg/Kg BW combined with high calcium milk. Bone density was determined using digital microradiography, the profile showed the increase of bone density in group that treated with combination of BPE 1000 mg/Kg BW and high calcium milk compare to control and given only milk groups. Docking molecular showed that BPE active compound which are hesperidin and naringin could have interaction with estrogen receptor Î± and Î². Overall, the result of this research showed that fortification of BPE with high calcium milk has good prospect to develop as effective therapy of osteoporosis.Â Keywords: Citrus maxima, phytoestrogen, osteoporosis, high calcium milk, estrogen receptor